RESEARCH AND EXPERIMENTAL DETERMINATION OF THERMO PHYSICAL PROPERTIESOF HIGHLY FOAMING SOLUTION - R.X., Musaeva.; S.K, Uvayzov.; N.X, Musaeva; F.S, Qo’ldosheva.; D.R, Akramov. (International Journal of Psychosocial Rehabilitation, 2020)
In the article discusses about basic properties of licorice root, and also, by experimental method, the basic thermophysical characteristics of licorice root are determind.